Ekofeminisme di Indonesia: Sebuah Kajian Reflektif atas Peran Perempuan Terhadap Lingkungan - Rr. Yudiswara Ayu Permatasari; Gede Agus Siswadi (Purwadita : Jurnal Agama dan Budaya, 2022)
The Covid-19 pandemic has given rise to various severe problems in Indonesia. It ranges from environmental issues to social issues. Women are the ones who feel the downturn as a result of this Covid-19 Pandemic. The downturn in life encourages people to rise and requires a mindset by the problems at hand. Ecofeminism is an ideology that is considered suitable for a country or a group of people to solve complex problems without harming various parties, including the environment. This paper seeks to explain the influence of ecofeminism in Indonesia to inspire the public that the ideology is by the culture and natural life in Indonesia and as an accelerator for the community's interests during the pandemic. The results obtained are the emergence of ecofeminism that is by people's lives in Indonesia and is not contradictory to the life of the nation and state.  Keywords: Ecofeminism, Women, Environment, Covid-19